A Model for Organizational Preparedness of SMEs During COVID-19 Pandemic in Kigezi Sub-region in South Western Uganda. - Tamwesigire, Caleb; Nafiu, Lukman Abiodun (Kabale University, 2023)
The outbreak of coronavirus disease (COVID-19) has severely affected the global and Uganda economy with major victims being small, and medium-sized enterprises (SMEs). The study examined and developed a model for organizational preparedness and business disaster of SMEs during COVID-19 pandemic in Kigezi sub-region in South Western Uganda. The specific objectives were to: (i)determine the characteristics of decision makers of SMEs during the COVID-19 pandemic; (ii) assess organizational features of SMEs during the COVID-19 pandemic; (iii) examine government response and preparedness of SMEs during the COVID-19 pandemic; and (iv) model the relationship between those factors identified with organizational preparedness and the management of SMEs during the COVID-19 pandemic. A cross-sectional survey research design was employed and interviewer-administered questionnaire as a research tool was used to elicit information from the managers of SMEs across the six (6) districts of Kigezi sub-region. Two-stage cluster sampling technique was used and the sample size was computed using Yamane’s sampling formulae based on a 5% level of precision. The value of CVI obtained was 0.840 while the value of reliability obtained was 0.770, which indicated that the questionnaire items were relevant and suitable for the study. Five hundred and ninety one (591) questionnaires were administered to the SME owners/managers while four hundred and seventy six (476) questionnaires were returned, giving the overall return rate as 81%. The study identifies the factors that were significant with organizational preparednessand the management of business during the COVID-19 pandemic in the Kigezi sub-region in South Western Uganda as firm size, firm financial condition, risk perception, government subsidy, help received from NGOs and the loan received from the bank/SACCO; while other factors: firm year of existence, source of initial capital, and gender of owners/managers were found to be insignificant. The results showed that organizational features, characteristics of decision makers and government response accounts for a total of 27.9% improvement on the management of business disaster in the Kigezi sub-region. The results further indicate that organizational features (β=0.163, p-value=0.000) and characteristics of decision makers (β=0.021, p-value=0.648) have positive but significant effect while government response (β=-0.780, p-value=0.682) have negative but no significant effect on the management of business disaster. The study concludes that organizational features and characteristics of decision makers are important factors that affected the organizational preparedness and the management of business during COVID-19 pandemic in Kigezi sub-region in South Western Uganda. The study recommends that SME owners/managers should focus on improving their firms’ features; perfect the way they make decision by providing a critical dynamic resilience strategy framework to manage their SMEs during the crisis period. There is also need for government/NGO interventions in the area of subsidy for SME owners/managers during the pandemic to boost their businesses. Keywords: Organizational Features, Business Disaster, Decision makers, Pandemic, COVID